Low serum progesterone affects live birth rate in cryopreserved blastocyst transfer cycles using hormone replacement therapy. Issue 3 (March 2022) - Maignien, Chloé; Bourdon, Mathilde; Marcellin, Louis; Laguillier-Morizot, Christelle; Borderie, Didier; Chargui, Ahmed; Patrat, Catherine; Plu-Bureau, Geneviève; Chapron, Charles; Santulli, Pietro
Abstract: Research question: Does serum progesterone concentration on the day of vitrified–warmed embryo transfer affect live birth rate (LBR) with hormonal replacement therapy (HRT) cycles? Design: Observational cohort study of patients ( n  = 915) undergoing single autologous vitrified–warmed blastocyst transfer under HRT using vaginal micronized progesterone. Women were included once, between January 2019 and March 2020. Serum progesterone concentration was measured by a single laboratory on the morning of embryo transfer. The primary end point was LBR. Univariate and multivariate logistic regression models were used for statistical analyses. Results: Median (25th–75th percentile) serum progesterone concentration on the day of embryo transfer was 12.5 ng/ml (9.8–15.3). The LBR was 31.5% (288/915) in the overall population. No significant differences were found in implantation rates (40.7% versus 44.9%); LBR was significantly lower in women with a progesterone concentration ≤25th percentile (≤9.8 ng/ml) (26.1% versus 33.2%, P = 0.045) versus women with a progesterone concentration >25th percentile. This correlated with a significantly higher early miscarriage rate (35.9% versus 21.6%, P  = 0.005). After adjusting for potential confounding factors in multivariate analysis, low serum progesterone levels (≤9.8 ng/ml) remained significantly associated with lower LBR (OR 0.68 95% CI 0.48 to 0.97). Conclusion: A minimum serum progesterone concentration is needed to optimize reproductive outcomes in HRT cycles with single autologous vitrified–warmed blastocyst transfer. Whether modifications of progesterone administration routes, dosage, or both, can improve pregnancy rates needs further study so that treatment of patients undergoing HRT cycles can be further individualized.